Codification and Reform of Islamic Family Law in the Republic of Tunisia: An Analysis of Marriage and Inheritance - Nandang Kusnadi; Abid Abid; Edi Rohaedi (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2026)
The purpose of this study is to examine Islamic family law in Tunisia, which is considered unique due to Tunisia's radicalism. This study is directed at library research and data collection is carried out using documentation methods sourced from documents relevant to the problem being studied. The analysis used is content analysis. The conclusion of this study is that the process of formulating and structuring Islamic family law in Tunisia is not merely an effort to codify (book) Maliki school of jurisprudence, but also takes progressive and revolutionary steps in an effort to legalize and regulate administration in the legal field, particularly Family Law. In addition, nationalists with secular educational backgrounds also participated in legal reforms carried out by the Tunisian government.